The Effect of Technology Acceptance, Electronic Words of Mouth, and Trust on Airlines Ticket Purchase Decision - Reni Dian Octaviani; Aisyah Rahmawati; Undang Juju; Edi Abdurachman; Ika Utami Yulihapsari (Indonesian Journal of Sustainability Accounting and Management, 2024)
This study aims to investigate the impact of technology acceptance (UTAUT) variables, Electronic Word of Mouth (EWOM), and trust on online airline ticket purchasing decisions in Indonesia. A purposive sampling technique was employed to collect data from 253 respondents through an online survey. The study utilized structural equation modeling to analyze the data. The findings reveal that performance expectancy, effort expectancy, facilitating conditions, and EWOM significantly influence online purchase decisions, while social influence has no significant impact. Trust emerges as a critical mediator in the relationship between these variables and purchasing decisions. This study contributes to the understanding of online consumer behavior and provides valuable insights for airline companies and online travel agencies to enhance their strategies. By extending the UTAUT model with EWOM and trust, this research offers a deeper understanding of online airline ticket purchasing behavior in the Indonesian context.